The concept of 'joy' in Old and Middle English. A semantic analysis - Fabiszak, Małgorzata (Wyższa Szkoła Biznesu w Pile, 2001)
The aim of this work is to arrive at a description of the semantic structure of the concept of 'joy' in OE and ME periods as well as to pinpoint changes that the concept underwent over this time. The concept of 'joy' is here understood as a mental representation of the meaning of a lexical field. In the present study only the core members of the field will be analysed for OE. These have been identified as bliss, blithe, dream, glaednes, liss, mirhth and wynsumnesse. The development of these words will be traced on into ME, even if the words show signs of falling out of the field of 'joy', i.e. I will in this respect be adopting a semasiological approach to the change of meaning. New words borrowed into ME to designate the conceptof'joy', such as cheer, delight, gay (gainess) and joy, will also be investigated, I will thus also be incorporating an onomasiological perspective. The choice of this particular field is based on the suggestion that it is relatively poorly described in the history of the English language (cf Strite 1989 on OE, Diller 1992). A number of works have been devoted to other emotion words, 'gloom' in particular (for example: Lochrie 1986, Magennis 1986). Those studies which have dealt with 'joy', however, have either investigated it with a different aim in mind (Ostheeren 1964) or focused on other lexical items (Fell 1982-83).
Keywords: joy; Old English; Middle English; lexical semantics; historical semantics